ANALOG-DIGITAL SELF-LEARNING FUZZY SPIKING NEURAL NETWORK AND ITS LEARNING ALGORITHM BASED ON ‘WINNER-TAKES-MORE’ RULE - Bodyanskiy, Ye.; Dolotov, A. (Radio Electronics, Computer Science, Control, 2010)
Analog-digital architecture of self-learning fuzzy spiking neural network is proposed in this paper. Spiking neuron synapse and some are treated in terms of classical automatic control theory. Conventional unsupervised learning algorithm of spiking neural network is improved by applying ‘Winner-Takes-More’ rule.